PENGEMBANGAN MODUL TERINTEGRASI PENDIDIKAN KARAKTER PADA POKOK BAHASAN KESETIMBANGAN KIMIA - Sarah Gusma; Betty Holiwarni; Johni Azmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to develop an integrated character education module on valid and practical subject of chemical equilibrium. This development research uses ADDIE model that has 5 stages, Analysis,Design, Development,Implementation and evaluation, but the research only arrived at the Development stage because the purpose of the research was to develop a valid and practical integrated character education module. To produce a valid module, a module validity test was carried out covering four aspects of assessment, namely aspects of content feasibility, linguistic aspects, presentation aspects and graphic aspects. To see the practicality of the module, limited testing was done at SMAN 6 Pekanbaru and SMAN 12 Pekanbaru. The results of the study that have been validated by 3 validators state that the percentage is 93,75%. The results of the test questionnaire were limited to 30 students, 89,58% and the results of the responses from 2 chemistry teachers were 93,5%. Based on the principle of validation and limited testing, the integrated module on character education on the subject of chemical equilibrium was declared valid and practical.Key Words: Modules, Character Education, Chemical Equilibrium